The impact of the financial crisis on insider trading profitability in Belgium - Geyt, Debby Van; Cauwenberge, Philippe Van; Bauwhede, Heidi Vander (Journal of Business Economics and Management, 2013)
The 2007 global financial crisis led to a chaotic financial environment characterized by highly uncertain and volatile stock markets. This created additional uncertainty about the fundamental value of shares and potentially increased the benefit of inside information. In this paper, we use event study methodology to examine whether Belgian corporate insiders were able to benefit from these turbulent market conditions. Given the large weight of financial institutions, the Belgian stock market was especially vulnerable to the financial crisis and provides an interesting environment to test this hypothesis. Our results show that, while insiders are generally able to earn abnormal returns, these returns are significantly higher during the years of the financial crisis.First published online: 19 Oct 2012